Comparative Epigenomic Profiling of the DNA Methylome in Mouse and Zebrafish Uncovers High Interspecies Divergence - Zhang, Chi; Hoshida, Yujin; Sadler, Kirsten C. (Frontiers in Genetics, 2016)
The DNA methylation landscape is dynamically patterned during development and distinct methylation patterns distinguish healthy from diseased cells. However, whether these tissue-specific methylation patterns are conserved across species is not known. We used comparative methylome analysis of base-resolution DNA methylation profiles from the liver and brain of mouse and zebrafish generated by reduced representation bisulfite sequencing, to identify the conserved and divergent aspects of the methylome in these commonly used vertebrate model organisms. On average, 24% of CpGs are methylated in mouse livers and the pattern of methylation was highly concordant among 4 male mice from two different strains. The same level of methylation (24.2%) was identified in mouse brain. In striking contrast, zebrafish had 63% and 70% of CpG methylation in the liver and brain, respectively. This is attributed, in part, to the higher percentage of the zebrafish genome occupied by transposable elements (52% vs. 45% in mice). Thus, the species identity was more significant in determining methylome patterning than was the similarity in organ function. Common features across tissues and species comprised the exclusion of methylation from promoters and from CpG islands near transcription start sites, and the clustering of methylated CpGs in gene bodies and intragenic regions. These data suggest that DNA methylation reflects species-specific genome structure, and that DNA methylation in non-promoter regions may play a vital role in genome evolution.